Michael Vey : the prisoner of cell 25 - Evans, Richard Paul. (New York : Mercury Ink/Simon Pulse, 2011)
To everyone at Meridian High School, fourteen-year-old Michael Vey is nothing special, just the kid who has Tourette's syndrome. But in truth, Michael is extremely special--he has electric powers. Michael thinks he is unique until he discovers that a cheerleader named Taylor has the same mysterious powers. With the help of Michael's friend, Ostin, the three of them set out to discover how Michael and Taylor ended up with their abilities, and their investigation soon brings them to the attention of a powerful group who wants to control the electric teens-- and through them, the world.
"Ages 12 up"--Jacket.
Keywords: Teenagers -- Juvenile fiction; Friendship -- Juvenile fiction; Great powers -- Juvenile fiction; Electricity -- Juvenile fiction; Tourette syndrome -- Juvenile fiction; Prisoners -- Juvenile fiction; Teenagers -- Fiction; Friendship -- Fiction; Great powers -- Fiction; Electricity -- Fiction; Tourette syndrome -- Fiction; Prisoners -- Fiction; Science fiction; Science fiction